OPTIMALISASI POTENSI MUSEUM KARST DALAM RANGKA MENINGKATKAN PENGEMBANGANWISATA PENDIDIKAN DI KAWASAN KARST PRACIMANTORO - , Elisa Dwi Rohani,SE ([Yogyakarta] : Universitas Gadjah Mada, 2013)
At this time the public began to lose cultural roots or identity, the museum can give you inspiration on the important things from the past that should be known to go into the future. Through the Year Visits Museum (TKM) in 2010 then express a National Move Love Museum (GNCM) are trying to put the museum in a very strategic position that serves to strengthen, understanding, appreciation, and concern for the development of cultural identity and nation should wake up at all order components of the Indonesian people, both on a local, regional and national levels. In this research method used is descriptive method is a method based on problem solving based on the facts at the time of the study and the form of words written or spoken of the people and the observed behavior. Descriptive method is used to portray the condition of ecosystems, hydrology, geology, biodiversity, the potential social, cultural and economic development around the Museum of Karst and Karst Museum portray the impact of development on the improvement of education in the district Wonogiri. This study aimed to assess the potential in the region Karst Museum that can be used to enhance the educational tour in Wonogiri. Specific objectives to be achieved in this research is to identify potential appeal in the region Karst Museum and attractions, amenity and accessibility toward Karst Museum, know the market share of travelers in Karst Museum, as well as evaluating the management of Karst Museum as a tourist attraction education. Methods The study uses descriptive method with visitors sampling the Simple Random Sampling through the interview method. Method of data retrieval through the deployment of questionnaires to 95 visitors (based Slovin) and surrounding communities Karst Museum Based on the results Karst Museum in Pracimantoro presence as an asset and a source of knowledge to learning of Geology for students and students so far have not been able to run properly. Optimizing Karst Museum as a source of knowledge and advice knowladge need to plan in order to improve the collection, enhanced functionality and improved educational services for tourist activities. Optimization of Karst Museum can be done by increasing the activity or attraction to do in Karst Museum, as well as add and inventory existing collection at the Museum of Karst so boring to end action.